2015
DOI: 10.1016/j.aop.2015.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the photonic band structure topology of a honeycomb lattice in an atomic vapor

Abstract: In an atomic vapor, a honeycomb lattice can be constructed by utilizing the three-beam interference method. In the method, the interference of the three beams splits the dressed energy level periodically, forming a periodic refractive index modulation with the honeycomb profile. The energy band topology of the honeycomb lattice can be modulated by frequency detunings, thereby affecting the appearance (and disappearance) of Dirac points and cones in the momentum space. This effect can be usefully exploited for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In particular, Longhi [48] showed that a modulation of the resonant frequencies of the coupled cavities in an optical lattice as an alternative to time modulation of hopping rates is sufficient to generate a synthetic gauge field for light. Outside of coupled waveguide arrays, recent work has demonstrated topological effects arising in atomic vapours [49], and optical Bloch oscillations and Zener tunnelling [50] as well as demonstration of edge states in dynamical superlattices [51]. Finally, we note that most previous works have focused solely on the regime where the modulation strength is far less than the modulation frequency [52,53], allowing for the application of the rotating-wave approximation.…”
Section: Dynamic Modulationmentioning
confidence: 91%
“…In particular, Longhi [48] showed that a modulation of the resonant frequencies of the coupled cavities in an optical lattice as an alternative to time modulation of hopping rates is sufficient to generate a synthetic gauge field for light. Outside of coupled waveguide arrays, recent work has demonstrated topological effects arising in atomic vapours [49], and optical Bloch oscillations and Zener tunnelling [50] as well as demonstration of edge states in dynamical superlattices [51]. Finally, we note that most previous works have focused solely on the regime where the modulation strength is far less than the modulation frequency [52,53], allowing for the application of the rotating-wave approximation.…”
Section: Dynamic Modulationmentioning
confidence: 91%
“…However, by employing two-photon Doppler-free configurations as well as EIT, enhanced nonlinear processes due to atomic coherence have been experimentally demonstrated 24 . The essentials of such enhanced nonlinear optical processes are the enhanced nonlinear susceptibility due to atomic coherence, slowed light beam propagation in the atomic medium, and greatly reduced linear absorption of the generated optical field due to EIT, which enable us to investigate the topological photonic problems in atomic ensembles 25 26 .…”
mentioning
confidence: 99%